Recognition and accounting valuation of intellectual capital: A conceptual and normative revision [Reconocimiento y valoración contable del capital intelectual: Una revisión conceptual y normativa] (2019)
The financial statements that are the result of the accounting and financial process do not reveal all the information that a company and its users need to make decisions, for example the intellectual capital that the company has generated in the normal course of its operation is not disclosed. Therefore, the objective of this paper is to conduct a conceptual review of intellectual capital, its management and models, as well as the accounting regulations applicable in Colombia, specifically for the issue of intangible assets. © 2019.